Reiterated homogenization of nonlinear monotone operators in a general deterministic setting - Dag Lukkassen; Gabriel Nguetseng; Hubert Nnang; Peter Wall (Journal of Function Spaces and Applications)
We study reiterated homogenization of a nonlinear non-periodic elliptic differential operator in a general deterministic setting as opposed to the usual stochastic setting. Our approach proceeds from an appropriate notion of convergence termed reiterated Σ-convergence. A general deterministic homogenization theorem is proved and several concrete examples are studied under various structure hypotheses ranging from the classical periodicity hypothesis to more complicated, but realistic, structure hypotheses.